Development of enzymatic cocktails for modification of xylan and production of derivatives - Bueno, Danilo [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The recalcitrance of lignocellulosic biomass has been indicated as a barrier to the technical-economical feasibility of the process of macromolecules extraction and production of high-added value products. Naturally, the lignocellulosic materials are resistents to enzymatic and microbian degradation, which occurs due to the organization of its components, where the cellulose is embedded in a matrix composed of hemicellulose and lignin. Therefore, extracting the hemicellulose from sugar cane bagasse without residual lignin is a great challenge. The xylan has several applications, depending on its structure: polymeric, oligomeric, monomeric, with or without branching/pending groups (xylooligosaccharides, xylose, hydrogels, packaging, artificial skin, etc.). An alternative approach to the chemistry pathway is to develop an enzymatic cocktail capable of: (1) complete hydrolysis of xylan, containing enzymes that cleave linkages of both the main chain and its pendant groups; (2) cleaving the bonds with the pendant groups, generating a free xylan chain of pendant groups; (3) cleaving different bonds in the main chain generating products with different degree of polymerization; (4) cleaving bonds between the xylan chain and the residual lignin. In this context, this project developed two enzymatic cocktails capable to lead xylan for complete hydrolysis removing the main chain and pendent groups with the use xylanase, β-xylosidase, and accessory enzymes. Through this study was possible to obtain XOS in higher content of concentration 19.6 g/L and with yield of 93%. Also, with this study it was possible to obtain a delignified xylan that presented interesting results as a substrate for xylanase activity (700 IU/mL) and for the growth of Aspergillus versicolor, which produced the xylanase enzyme with high activity (1350 IU/mL) in the presence of this substrate over 10 days. The bioplastics produced in this study using xylan modified via enzymatic hydrolysis (B2-lacase and B4-arabinofuranosidase) and chemical treatment (B3-H2O2) with the addition of starch, glycerol, and bis-acrylamide, presented as an interesting approach due to the observed improvements in the properties of the bioplastic when compared to original xylan (B1). The results indicated low opacity, moisture retention, solubility, and major tensile stress compared to the B1 bioplastic, possibly due to the removal of lignin and arabinose pendant groups, including the use of bis-acrylamide in the formulation of the bioplastics. Therefore, this project is a pioneer in production of value-added products derivates from xylan of sugarcane bagasse, such as two robust enzymatic cocktails to XOS production. In addition, obtaining bioplastics derived from delignified xylan and without arabinose, the xylan modification promotes an substrate for the growth of A. versicolor and also for determining the enzymatic activity of xylanase.

A recalcitrância da biomassa lignocelulósica é uma barreira à viabilidade técnico-económica do processo de extracção de macromoléculas e produção de produtos de alto valor agregado. Naturalmente, os materiais lignocelulósicos são resistentes a degradação enzimática e microbiana, que ocorre devido a organização dos seus componentes, onde a celulose está embutida numa matriz composta de hemicelulose e lignina. Portanto, a extração da hemicelulose do bagaço de cana de açúcar sem lignina residual é um grande desafio. A xilana tem várias aplicações, dependendo da sua estrutura: polimérica, oligomérica, monomérica, com ou sem grupos ramificados/pendentes (xiloligossacarídeos, xilose, hidrogel, embalagens, pele artificial, etc.). Uma abordagem alternativa a via química é desenvolver um coquetel enzimático capaz de: (i) completa hidrólise da xilana, contendo enzimas que clivam as ligações tanto da cadeia principal como os seus grupos pendentes; (ii) clivagem das ligações com os grupos pendentes, gerando uma xilana livre de grupos pendentes; (iii) clivagem de diferentes ligações na cadeia principal gerando produtos com diferentes graus de polimerização; (iv) clivagem das ligações entre a cadeia xilana e a lignina residual. Neste contexto, este estudo desenvolveu dois coquetéis enzimáticos capazes de levar a xilana a uma completa hidrólise removendo a cadeia principal e grupos pendentes com o uso de xilanase, β-xilosidase e enzimas acessórias. Através deste estudo foi possível obter XOS com concentração de 19,6 g/L e rendimento de 93%. Além disso, foi possível obter uma xilanase deslignificada que apresentou resultados interessantes como substrato para a atividade de xilanase (700 UI/mL) e para o crescimento de Aspergillus versicolor, que produziu a xilanase com alta atividade (1350 UI/mL) na presença deste substrato durante 10 dias. Os bioplásticos produzidos neste estudo utilizando xilana modificada por hidrólise enzimática (B2-lacase e B4-arabinofuranosidase) e tratamento químico (B3-H2O2) com adição de amido, glicerol e bis-acrilamida, apresentaram-se como uma abordagem interessante devido as melhorias observadas nas propriedades do bioplástico quando comparado com a xilana original (B1). Os resultados indicaram baixa opacidade, retenção de humidade, solubilidade, e grande tensão de tração em comparação com o bioplástico B1, possivelmente devido à remoção de lignina e dos grupos pendentes de arabinose, incluindo a utilização de bis-acrilamida na formulação dos bioplásticos. Portanto, este estudo é pioneiro na produção de produtos de alto valor agregado derivados da xilana do bagaço da cana de açúcar, tais como dois robustos coquetéis enzimáticos para a produção de XOS. Além disso, a obtenção de bioplásticos derivados de xilana delignificada mostraram-se eficazes como substrato para o crescimento de A. versicolor e também para determinar a atividade enzimática da xilanase.
Desenvolvimento de coquetéis enzimáticos para modificação de xilana e produção de derivados
Keywords: Enzymatic extracts; Xylanases; Auxiliary enzymes; Heterologous expression; Xylooligosaccharides; Hydrogels; Extratos enzimáticos; Xilanases; Enzimas auxiliares; Expressão heteróloga; Hidrogéis; Xilooligossacarídeos